Pengaruh Variasi Tekanan pada Produksi Komposit Friction Materials Kampas Rem terhadap Sifat Mekanik, Fisik dan Tribologi: indonesia - Fauzi, Akhmad; Wibowo, Muhammad Errizky; Admoko, Mohammad Rizky Djati; Khafidh, Muhammad; Fitriyana, Deni Fajar; Siregar, Januar Parlaungan (UII, 2026)
This study develops environmentally friendly brake pads from rice husk with phenolic resin as a binder material. This study aims to analyze the influence of compression pressure on the properties of mechanical, physical and tribological performance. In this study, brake friction material was made using the compression molding method with a composition of 40% phenolic resin, 20% rice husk, 15% , 15% dan 10% hexamine. The compression pressures are varied, i.e. 5 MPa, 10 MPa and 15 MPa. Testing includes density, impact strength, tensile strength, flexural strength, wear and friction. The results showed that increasing the material compaction compression pressure from 5 MPa to 10 MPa can reduce the density, impact strength, tensile strength, flexural strength, and specific wear rate. Meanwhile, increasing the compaction compression pressure from 10 MPa to 15 MPa can improve properties of mechanical, physical and wear resistance. The final material result due to increased compaction compression pressure is influenced by particle size, matrix and filler distribution, porosity along resin cross-linking.